2009
DOI: 10.1097/mcp.0b013e3283218603
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and copeptin: prognostic predictors in chronic obstructive pulmonary disease exacerbations

Abstract: Further studies are needed to determine the role of CRP and copeptin as biomarkers that aid in diagnosis and clinical outcome in acute exacerbation of COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 36 publications
1
13
1
2
Order By: Relevance
“…It has been established in previous studies that various inflammatory markers like C-reactive protein (CRP), fibrinogen and leucocyte count increase in stable patients of COPD and that this increase is associated with the negative results of the disease [7][8][9][10]. Moreover, it has been described that elevated CRP levels can be used in the diagnosis of acute exacerbation and to approximate the prognosis of the disease [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been established in previous studies that various inflammatory markers like C-reactive protein (CRP), fibrinogen and leucocyte count increase in stable patients of COPD and that this increase is associated with the negative results of the disease [7][8][9][10]. Moreover, it has been described that elevated CRP levels can be used in the diagnosis of acute exacerbation and to approximate the prognosis of the disease [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…So, nowadays, being able to measure the copeptin level simply and quickly encourages most clinicians to investigate the vasopressin system in various clinical conditions. For instance, copeptin was shown to be increased during acute exacerbation of chronic obstructive pulmonary disease [25]. In another study, Morgenthaler et al [26] studied copeptin in hemorrhagic and septic shock patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, increased serum CRP levels have been extensively evaluated as a marker of systemic infl ammation in COPD exacerbations (19,20). Current studies have reported that CRP alone is neither sensitive nor specifi c in predicting clinical severity or outcome of COPD exacerbations and speculate that utilizing combinations of biomarkers may prove more useful (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%